Best method for analysis of brain oscillations in healthy subjects and neuropsychiatric diseases - Turp Gölbaşı, Bilge; Tülay, Elif; Aydın, Serap; Başar Eroğlu, Canan; BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2016)
The research related to brain oscillations and their connectivity is in a new take-off trend including the applications in neuropsychiatric diseases. What is the best strategy to learn about functional correlation of oscillations? In this report, we emphasize combined application of several analytical methods as power spectra, adaptive filtering of Event Related Potentials, inter-trial coherence and spatial coherence. These combined analysis procedure gives the most profound approach to understanding of EEG responses. Examples from healthy subjects, Alzheimer's Diseases, schizophrenia, and Bipolar Disorder are described. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Event-related potentials; Event-related oscillations; Inter-trial coherence; Coherence; Adaptive filtering; Alzheimer's diseases; Schizophrenia; Bipolar disorder; Mild Cognitive Impairment; Event-Related Potentials; Visual Oddball Paradigm; Recorded Eeg-Epograms; Alzheimers-Disease; Bipolar Disorder; Evoked-Potentials; Wavelet Entropy; Gamma-Responses; Resting Eeg